2017
DOI: 10.1177/1060028017739325
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Adherence to the 2013 ACC/AHA Cholesterol Guideline in a Teaching Versus Nonteaching Outpatient Clinic

Abstract: The overall adherence rate to the 2013 ACC/AHA cholesterol guideline from this nonteaching outpatient clinic was significantly lower than that previously observed in a teaching outpatient clinic. The single pharmacist-led seminar did not significantly affect prescribers' adherence rate to the guideline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Pharmacist interventions can take a leading role in facilitating adherence to perioperative antibiotic prophylaxis guidelines in Africa and improving adherence to recommended amiodarone monitoring guidelines . However, it was also reported that pharmacist intervention did not increase adherence to guideline‐directed statin therapy, and pharmacist intervention did not significantly affect prescribers' adherence rate to the 2013 American college of cardiology/American heart association cholesterol guideline . To the best of our knowledge, no pharmacist‐led intervention on TXA treatment has been reported, besides one pre‐hospital administration protocol where the pharmacist was responsible for expediting the delivery of TXA to the trauma bay …”
Section: Introductionmentioning
confidence: 99%
“…Pharmacist interventions can take a leading role in facilitating adherence to perioperative antibiotic prophylaxis guidelines in Africa and improving adherence to recommended amiodarone monitoring guidelines . However, it was also reported that pharmacist intervention did not increase adherence to guideline‐directed statin therapy, and pharmacist intervention did not significantly affect prescribers' adherence rate to the 2013 American college of cardiology/American heart association cholesterol guideline . To the best of our knowledge, no pharmacist‐led intervention on TXA treatment has been reported, besides one pre‐hospital administration protocol where the pharmacist was responsible for expediting the delivery of TXA to the trauma bay …”
Section: Introductionmentioning
confidence: 99%